2021
DOI: 10.1101/2021.09.08.21254232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study of REM sleep behavior disorder identifies novel loci with distinct polygenic and brain expression effects

Abstract: REM sleep behavior disorder (RBD) represents both an early marker and key symptom of synucleinopathies, mainly Parkinson disease (PD) and Lewy body dementia (LBD), and a strong opportunity for early clinical intervention for these conditions. Yet, the genetics of RBD are currently not well characterized. In this study, we perform the first genome-wide analyses on RBD, including genome-wide association study, pathway analysis, heritability, genetic correlation, and mendelian randomization. We report two novel R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…iRBD likely has a distinct genetic risk profile compared with overt α‐synucleinopathies, with evidence of both overlapping and contrasting risk loci across the conditions. RBD heritability, explained by common variants, is estimated at 12.3%, which is similar to the current estimation for DLB, and five RBD genetic loci have been identified by a genome‐wide association study (GWAS) (Krohn et al, 2021). These genes are concentrated in the autophagy‐lysosomal pathway (ALP) and are more specific to this pathway than any similarly powered GWAS of PD or DLB.…”
Section: Video‐polysomnography (V‐psg) As a Diagnostic Requirement An...supporting
confidence: 78%
See 2 more Smart Citations
“…iRBD likely has a distinct genetic risk profile compared with overt α‐synucleinopathies, with evidence of both overlapping and contrasting risk loci across the conditions. RBD heritability, explained by common variants, is estimated at 12.3%, which is similar to the current estimation for DLB, and five RBD genetic loci have been identified by a genome‐wide association study (GWAS) (Krohn et al, 2021). These genes are concentrated in the autophagy‐lysosomal pathway (ALP) and are more specific to this pathway than any similarly powered GWAS of PD or DLB.…”
Section: Video‐polysomnography (V‐psg) As a Diagnostic Requirement An...supporting
confidence: 78%
“…Additionally, prominent PD genes such as LRRK2 (Fernandez‐Santiago et al, 2016), MAPT , and autosomal recessive genes (Mufti, Rudakou, et al, 2021a) are not associated with isolated RBD. A similar pattern is found between RBD and DLB, where ALP genes SNCA , GBA , and TMEM175 are shared risk factors in both conditions, however, DLB genes APOE and BIN1 (Chia et al, 2021) are not associated with RBD (Gan‐Or et al, 2017; Krohn et al, 2021). Mutations in PSAP , encoding for saposin C, a lysosomal activator of GBA , have also been implicated in iRBD (Sosero et al, 2022), as well as rare variants in LAMP3 (encoding the lysosomal associated membrane protein 3) and other genes (Mufti, Yu, et al, 2021b).…”
Section: Video‐polysomnography (V‐psg) As a Diagnostic Requirement An...mentioning
confidence: 66%
See 1 more Smart Citation
“…White matter abnormalities and topological disorganization of grey matter have been reported in iRBD, 8, 58, 79, 80 as well as a genetic makeup more complex than the sole effects of SNCA and GBA . 81 Once these changes are more thoroughly understood in iRBD, they can be implemented in the model.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous evidence has shown that iRBD and synucleinopathies share a partial genetic overlap. 3 While particular loci (SNCA, GBA, and TMEM175) were shared between these traits, distinct loci such as LRRK2 and MAPT for PD and APOE LBD were also identified. 3 Furthermore, while the SNCA locus is essential in PD, LBD, and iRBD, the association with SNCA is driven by different variants for the different traits.…”
Section: Introductionmentioning
confidence: 97%